2021
DOI: 10.1111/bjh.17412
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of daratumumab in patients with multiple myeloma and severe renal failure

Abstract: Cr, creatinine; dFLC, difference between involved free light chain (FLC) and uninvolved FLC; eGFR, estimated glomerular filtration rate; iFLC, involved FLC; NA, not available; no., number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…In this study, the overall response rate was 40%, the median PFS was 8.74 months, and the median overall survival was 12.2 months with tolerable grade 3-4 adverse events of thrombocytopenia (n = 5), anemia (n = 4), and neutropenia (n = 4). In addition, in Japan, a case series of 13 RRMM patients with an eGFR <15 treated with Dara was reported [13]. In this report, 10 of 13 patients had a >50% reduction of involved FLC.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, the overall response rate was 40%, the median PFS was 8.74 months, and the median overall survival was 12.2 months with tolerable grade 3-4 adverse events of thrombocytopenia (n = 5), anemia (n = 4), and neutropenia (n = 4). In addition, in Japan, a case series of 13 RRMM patients with an eGFR <15 treated with Dara was reported [13]. In this report, 10 of 13 patients had a >50% reduction of involved FLC.…”
Section: Discussionmentioning
confidence: 65%
“…Notably, 3 of 6 previously dialysis-dependent patients achieved independence from dialysis. 10 The safety of daratumumab and its contribution to renal function improvement have also been emphasized in some case reports. 2,3,11 In our study, we similarly observed a degree of anti-myeloma efficacy, reporting complete remission in 1 patient and very good partial remission in 4 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world experience with daratumumab monotherapy has continuously been reported since its approval as a treatment for RRMM [ 10 - 13 ]. The studies highlighted that daratumumab monotherapy was safely administered to patients, including those who did not fit the clinical trials selection criteria.…”
Section: Discussionmentioning
confidence: 99%